'A warning in the shape of the novel' – the relevance of lessons contained in F. Dostoyevsky's The Possessed for twenty-first-century United States. Issue 3 (1st September 2017) - Akroyd, Olga
The Possessed (1872) by F. Dostoyevsky is a key text for comprehending the mechanisms behind the emergence and development of public disorder in an enclosed urban setting. Dubbed a 'roman-preduprezhdenie' or 'a warning in the shape of a novel' for the generations to come, it can easily be described as one of the author's most political and complex works that retains specific relevance for the present-day world. This article attempts to collect and analyse several major lessons regarding the origins and development of urban violence and rioting to be gleaned from Dostoyevsky's text, and apply them to the modern-day American case studies of social protesting and public unrest (namely, the Ferguson riots and the Occupy movement, 2011 onward). By doing so, I will draw a conclusion relevant for the modern leaders, scholars and thinkers preoccupied with the notions of urban rioting and violence.